Welfare impacts of drought adaptation strategies in John Taolo Gaetsewe district, Northern Cape Province, South Africa (Research in Agriculture Livestock and Fisheries, 2024)
Drought is a global problem that presents a negative impact on the welfare of millions of people in both industrialized and developing nations. In South Africa, poor rural households, who depend on rain-fed subsistence agriculture for their livelihoods are the most susceptible to drought, and have the least ability to absorb its impacts. The primary goal of this study was to analyse the effects of drought adaptation strategies on rural households’ welfare and to compute the welfare enhancement impacts that are associated with each adaptation method. The study was conducted in John Taolo Gaetsewe district, Northern Cape province. Multistage sampling technique was used to sample 360 rural households, who were affected by drought. The results showed that the average age of households’ heads was 52 years. Only 41% of the households’ heads had an education level between Grades 8 and 12, and about 63% were male. Average farming experience was 7.67 years and pensioners made up about 47%. Also, 65% of households’ heads depended on government assistance, while 85% lacked access to formal credit. The 2SLS results showed that household income, household size, pension, grant, and use of crop diversification significantly influenced per capita consumption expenditure. The results showed that average treatment effect (ATE) from crop diversification was R497.16 and statistically significant (p